Harmonics Reduction of a single Phase Half Bridge Inverter (Global Journals of Research in Engineering, 2013)
This paper presents an approach to minimize the harmonics contained in the output of a single phase half bridge inverter. With a view to reducing harmonics an LC low pass filter is used which blocks the harmonics and undeniably passes almost sinusoidal output at the output terminal. An illustration of Fourier Transform has been provided in this paper in order to perceive both the fundamental and harmonics component precisely. It has been found from simulation that the Total Harmonic Distortion (THD) before and after the application is 44.999% and 0.0183% respectively. That is why, this LC low pass filter is quite effective to reduce THD of a 1-phase half bridge inverter.
Keywords: single phase half bridge inverter; IGBT; harmonics analysis; FFT; THD; LC low pass filter; MATLAB simulation